Task shifting – Ghana's community mental health workers’ experiences and perceptions of their roles and scope of practice - Agyapong, Vincent I. O. (Glob Health Action, 2015)
BACKGROUND: Because of the absence of adequate numbers of psychiatrists, the bulk of mental health care at the community level in Ghana is provided by community mental health workers (CMHWs). OBJECTIVE: To examine the role and scope of practice of CMHWs in Ghana from their own perspectives and to make recommendations to improve the care they provide. DESIGN: We conducted a cross-sectional survey of 164 CMHWs from all the 10 administrative regions of Ghana, comprising 71 (43.3%) community psychiatric nurses (CPNs), 19 (11.6%) clinical psychiatric officers (CPOs), and 74 (45.1%) community mental health officers (CMHOs). RESULTS: Overall, only 39 (23.8%) CMHWs worked closely with psychiatrists, 64 (39%) worked closely with social workers, 46 (28%) worked closely with psychologists and 13 (7.9%) worked closely with occupational therapists. A lower proportion of CMHOs worked closely with psychiatrists, psychologists, and social workers compared with CPOs and CPNs. There was no significant difference in the proportion of the different CMHW types who expressed confidence in their ability to diagnose any of the commonly named mental health conditions except personality disorders. However, a lower proportion of CMHOs than CPOs and CPNs expressed confidence in their ability to treat all the disorders. The CMHWs ranked schizophrenia as the most frequently treated mental health condition and there was no statistically significant difference in the reported frequency with which the three groups of CMHWs treated any of the mental health conditions. CONCLUSIONS: Mental health policy makers and coordinators need to thoroughly review the training curriculum and also evaluate the job descriptions of all CMHWs in Ghana to ensure that they are consistent with the demands and health-care needs of patients they care for in their communities. For example, as CMHOs and CPNs prescribe medication even though they are not expected to do so, it may be worth exploring the merits of including the prescription of common psychotropic medication in their training curriculum and job descriptions.